2019
DOI: 10.1167/iovs.18-25786
|View full text |Cite|
|
Sign up to set email alerts
|

Apolipoprotein A-I Mimetic Peptide L-4F Removes Bruch's Membrane Lipids in Aged Nonhuman Primates

Abstract: PURPOSE. Multiple evidence lines support Bruch's membrane lipid deposition as a major precursor of soft drusen and age-related macular degeneration as including a potentially treatable atherosclerosis-like progression in the subretinal pigment epithelium (RPE)-basal lamina space. We evaluated the effect of anti-inflammatory, antiatherogenic peptide L-4F on Bruch's membrane of aged nonhuman primates in a dose-escalating study. METHODS. Macaca fascicularis ‡20 years of age evaluated by color fundus photography a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 112 publications
(112 reference statements)
0
20
0
Order By: Relevance
“…10,24,[34][35][36][37][38] In addition, type 1 CNV also obviates the interchange barrier due to an age-associated BrM change, which is characterized by an increased calcification of elastic fibers and accumulation of lipid rich extracellular deposits between the RPE basal lamina and the inner collagenous layer of BrM including basal linear deposits (BLinD) and soft drusen. [11][12][13][39][40][41][42] Potential therapeutic implications…”
Section: Discussionmentioning
confidence: 99%
“…10,24,[34][35][36][37][38] In addition, type 1 CNV also obviates the interchange barrier due to an age-associated BrM change, which is characterized by an increased calcification of elastic fibers and accumulation of lipid rich extracellular deposits between the RPE basal lamina and the inner collagenous layer of BrM including basal linear deposits (BLinD) and soft drusen. [11][12][13][39][40][41][42] Potential therapeutic implications…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been suggested that in hypoxic states and with ageing, the trophic effects of vascular endothelial growth factor (VEGF) A, which is secreted by the retinal pigment epithelium (RPE), on the choroid and CC in particular are disturbed by a thickened BM (Rudolf et al. ). Accordingly, histological studies demonstrated a decrease in CC diameter and choroidal thickness from the first to the tenth decade of life while the thickness of BM increases with age (Ramrattan et al.…”
Section: Discussionmentioning
confidence: 99%
“…Although eyes from WT mice exhibited normal RPE-choroid morphology with organized basal infoldings and apical processes of the RPE(Figure 5, M and N), in Nr1h3 -/mice, continuous sub-RPE deposits were observed below disrupted basal infoldings, seen as amorphous, electron-dense material, interspersed with "streamers," a phenotype typical of early dry AMD (over 40% of the length of Bruch's membrane, BrM;Figure 5, O and P, and SupplementalFigure 12). The RPE phenotype of Nr1h2 -/mice had distinct pathologies, including accumulation of large lipid droplets within the RPE, reminiscent of lipoidal degeneration, which is not a characteristic of AMD (Figure 5, Q and R, and refs 27,28)…”
mentioning
confidence: 99%